2012
DOI: 10.1016/j.ydbio.2012.01.027
|View full text |Cite
|
Sign up to set email alerts
|

An essential requirement for β1 integrin in the assembly of extracellular matrix proteins within the vascular wall

Abstract: β1 integrin has been shown to contribute to vascular smooth muscle cell differentiation, adhesion and mechanosensation in vitro. Here we showed that deletion of β1 integrin at the onset of smooth muscle differentiation resulted in interrupted aortic arch, aneurysms and failure to assemble extracellular matrix proteins. These defects result in lethality prior to birth. Our data indicates that β1 integrin is not required for the acquisition, but it is essential for the maintenance of the smooth muscle cell pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 57 publications
(91 reference statements)
9
39
0
Order By: Relevance
“…Itga5/av SM22-Cre embryos developed interrupted aortic arch type-B and a large aneurysm that encompassed the brachiocephalic artery and the proximal region of the right carotid artery. The same phenotype has been observed in mice that lack vSMC expression of all the β1 integrins (Turlo et al, 2012). This suggests that the phenotype of Itga5/ av SM22-Cre mice, and therefore the vSMC-specific Itgb1 mutant, is caused by the loss of α5β1 and specifically αvβ1, rather than any of the other αv (αvβ3, αvβ5, αvβ6 and αvβ8) or β1 (α1β1, α2β1, α3β1, α4β1, α6β1, α7β1, α9β1, α10β1, α11β1) integrin heterodimers.…”
Section: Cardiovascular Development Is Regulated By α5 and αV Integrinssupporting
confidence: 70%
See 1 more Smart Citation
“…Itga5/av SM22-Cre embryos developed interrupted aortic arch type-B and a large aneurysm that encompassed the brachiocephalic artery and the proximal region of the right carotid artery. The same phenotype has been observed in mice that lack vSMC expression of all the β1 integrins (Turlo et al, 2012). This suggests that the phenotype of Itga5/ av SM22-Cre mice, and therefore the vSMC-specific Itgb1 mutant, is caused by the loss of α5β1 and specifically αvβ1, rather than any of the other αv (αvβ3, αvβ5, αvβ6 and αvβ8) or β1 (α1β1, α2β1, α3β1, α4β1, α6β1, α7β1, α9β1, α10β1, α11β1) integrin heterodimers.…”
Section: Cardiovascular Development Is Regulated By α5 and αV Integrinssupporting
confidence: 70%
“…This suggests that the phenotype of Itga5/ av SM22-Cre mice, and therefore the vSMC-specific Itgb1 mutant, is caused by the loss of α5β1 and specifically αvβ1, rather than any of the other αv (αvβ3, αvβ5, αvβ6 and αvβ8) or β1 (α1β1, α2β1, α3β1, α4β1, α6β1, α7β1, α9β1, α10β1, α11β1) integrin heterodimers. Like Turlo et al (2012), we also found that migration and initiation of vSMC fate were unaffected by loss of α5 and αv integrins. vSMCs in Itga5/av mutants expressed high levels of the vSMC markers αSMA, SM22α and Myh11, and migrated efficiently to the PAAs and blood vessels within the skin.…”
Section: Cardiovascular Development Is Regulated By α5 and αV Integrinssupporting
confidence: 70%
“…Thus, the downregulation of integrins α5 and αv in Itga5/Itgav SM22-Cre double mutants has most likely occurred after the onset of VSMC differentiation in the NC, explaining the lack of VSMC differentiation defect in these mutants (Turner et al, 2015). Similarly, Turlo et al (2012) used the SM22α-Cre transgenic line to ablate integrin β1 and showed that the expression of β1-containing integrin heterodimers, which include α5β1, in smooth muscle cells was important for maintaining AAA VSMCs and AAA integrity. Taken together with the studies by Turlo et al (2012) and Turner et al (2015), our work demonstrates that signaling by Fn1 and integrin α5β1 is essential for both the morphogenesis and maintenance of the AAAs: our studies establish the requisite role of Fn1 and integrin α5β1 in the differentiation of NC cells into VSMCs, thereby regulating the remodeling of symmetrical PAAs into the AAAs.…”
Section: Early and Late Roles Of Fn1-binding Integrins In Aaa Morphogmentioning
confidence: 99%
“…Similarly, Turlo et al (2012) used the SM22α-Cre transgenic line to ablate integrin β1 and showed that the expression of β1-containing integrin heterodimers, which include α5β1, in smooth muscle cells was important for maintaining AAA VSMCs and AAA integrity. Taken together with the studies by Turlo et al (2012) and Turner et al (2015), our work demonstrates that signaling by Fn1 and integrin α5β1 is essential for both the morphogenesis and maintenance of the AAAs: our studies establish the requisite role of Fn1 and integrin α5β1 in the differentiation of NC cells into VSMCs, thereby regulating the remodeling of symmetrical PAAs into the AAAs. The work of Turlo et al (2012) and Turner et al (2015) demonstrated that following the differentiation of NC cells into VSMCs, signaling by α5-, αv-and β1-containing integrin heterodimers is essential for maintaining VSMCs and the architecture of the AAA vessel wall.…”
Section: Early and Late Roles Of Fn1-binding Integrins In Aaa Morphogmentioning
confidence: 99%
“…In postnatal retinal vasculature, integrin β1-mediated endothelial cell-ECM interactions were required for production and assembly of the ECM, as well as formation of stable, nonleaky blood vessels (11). Mural cells (pericytes and vascular smooth muscle cells) that encase blood vessels also must express integrin β1 for adhesion and spreading, as well as assembly of ECM proteins that stabilize blood vessel walls (12,13).…”
mentioning
confidence: 99%